Adoption of Laser Leveling in Vietnam and Cambodia - CGIAR Research Program on Rice (2019)
With the interventions of IRRI, Laser controlled land leveling (LLL) has been introduced and verified in the partner countries. The LLL adoption has been fostered through field demonstrations, training of stakeholders and support to local equipment supply chains. First users are machinery contract service providers and final users are farmers. As of 2019, LLL was applied for about 4,000 and 3,500 ha in Vietnam and Cambodia, respectively.